Understanding Regarding Combat Sports for Level II Physical Education Students, The Semester 4, 2024, Nusantara PGRI University of Kediri - Gilas, Gilas Pradana Putra; Setiawan, Irwan; Puspodari (CV. Nusantara Sporta, 2024)
The purpose of this research is to determine the level of understanding of Tarung Derajat martial arts among second-year Physical Education students in the 4th semester of 2024 at Universitas Nusantara PGRI Kediri. This study is a descriptive quantitative research. The population consists of all second-year Physical Education students in the 4th semester of 2024 at Universitas Nusantara PGRI Kediri. The sample was selected based on specific criteria, resulting in 60 respondents, with 10 students from each class (2A to 2F). Data were collected using a questionnaire instrument. The data were then analyzed using descriptive analysis techniques. The results of the research show that the majority of the students have a good understanding of Tarung Derajat martial arts. Most students stated that they enjoy participating in Tarung Derajat activities at UNP Kediri, which reflects their enthusiasm for the sport and its potential to become a platform for student achievement in the future. Additionally, most second-year students at UNP Kediri expressed their motivation to further develop specific sports disciplines.